The relationship between burnout, coping strategies and stress management strategies in health care professionals - Rus, Mihaela; Sandu, Mihaela Luminita; Manescu, Marina Alexandra (Technium Social Sciences Journal, 2022)
Burnout syndrome is lately more and more often encountered in national and even international scientific papers on different professional categories and hierarchical levels. In this research is targeted the medical staff of Medical-Social Care Unit, nurses, medical assistants and even doctors. Unit founded in 2007 that keeps the same staff since then, forming a familiar framework for both employees and beneficiaries and developing different skills for teamwork. Even since the pandemic, the rules became stricter and the entire staff was removed from their comfort zone which could lead to an imbalance in stress management and imprint on emotional state of the employees, therefore causing burnout. This research targets a single objective, specifically the relationship between burnout, cognitive-emotional coping strategies and professional stress management strategies, the hypotheses being formulated one by one considering the correlation of two variables.